The Dwellers of Mutasarrifate of Jerusalem (1917- 1874) Analysis Study - Yousef, Marwan Mohammad Hamdan; Mohd Nor, Mohd Roslan; Achour, Meguellati (Journal Al-Muqaddimah, 2017)
This article is about the dwellers of Mutasarrifate of Jerusalem and their number and the factors that affected them. The city has witnessed many events that affected the number of population who lived and settled in the city. It also witnessed the focus of Zionism to settle Jewish in the city, for the demographic change of population and making most them Jewish. Moreover, they made use of the unlimited support from the Western countries that had been motivated by the Jewish influence that was characterized by their financial control on the economies of those Western countries. There also were many other factors that affected the number of population other than the Jewish settlement, they had a direct influence in increasing and decreasing the population number which was characterized by the spread ÙˆÙ‡of diseases and natural disasters and the invasions of grasshoppers